Production of Dials for Analogue Electrical Measuring Instruments with Non-Linear Measuring Mechanism by Means of Laser Engraving - Aleksey Kirillov; Valerij Sakevich (Vestnik of Vitebsk State Technological University, 2017)
The subject of this research is a benchmark analysis of methods for single-item production of dials for electrical measuring instruments. The research was held with the aim to improve the quality of produced dials and also to enhance efficiency of printing the information signs and labels onto the dial.